ICT TPACK-Oriented of Floor Gymnastics Learning Media for Elementary School Students - Made Agus Wijaya Made; I Gede Suwiwa; Wahyu Indra Bayu; Erwin O Estrella (Universitas Pendidikan Ganesha, 2023)
Physical education teachers during the Covid-19 pandemic generally used textbooks and video tutorials to visualize basic gymnastic movements. It makes it difficult for students to learn. This study aims to develop information, communication and technology/ICT Technological Pedagogical and Content Knowledge/TPACK-oriented gymnastics basic skills learning media for high-grade elementary school students. This type of research is development. This development research uses the ADDIE model design, which focuses on the analysis and design stages discussion. Data collection methods are observation, interviews, and questionnaires. The data collection instrument is a questionnaire. Data analysis in this study was carried out using descriptive quantitative and qualitative analysis. The results showed that first, 342 people (82%) of elementary school students needed ICT TPACK-oriented gymnastics basic skills learning media. Based on data analysis and discussion, this study concludes that elementary school students need learning media for basic ICT TPACK-oriented gymnastics skills. The motion assignments are designed on a combination of basic movement materials using a jumping table, balance movements on the floor and kayaks that are varied by the curriculum, guaranteeing the adequacy of learning motion. Some characters are internalized, and the safety and security of students are guaranteed.